Overcoming technological barriers in microfluidics: Leakage testing - Silverio, Vania; Guha, Suvajyoti; Keiser, Armelle; Natu, Rucha; Reyes, Darwin R.; van Heeren, Henne; Verplanck, Nicolas; Herbertson, Luke H. (Frontiers in Bioengineering and Biotechnology, 2022)
The miniaturization of laboratory procedures for Lab-on-Chip (LoC) devices and translation to various platforms such as single cell analysis or Organ-on-Chip (OoC) systems are revolutionizing the life sciences and biomedical fields. As a result, microfluidics is becoming a viable technology for improving the quality and sensitivity of critical processes. Yet, standard test methods have not yet been established to validate basic manufacturing steps, performance, and safety of microfluidic devices. The successful development and widespread use of microfluidic technologies are greatly dependent on the community’s success in establishing widely supported test protocols. A key area that requires consensus guidelines is leakage testing. There are unique challenges in preventing and detecting leaks in microfluidic systems because of their small dimensions, high surface-area to volume ratios, low flow rates, limited volumes, and relatively high-pressure differentials over short distances. Also, microfluidic devices often employ heterogenous components, including unique connectors and fluid-contacting materials, which potentially make them more susceptible to mechanical integrity failures. The differences between microfluidic systems and traditional macroscale technologies can exacerbate the impact of a leak on the performance and safety on the microscale. To support the microfluidics community efforts in product development and commercialization, it is critical to identify common aspects of leakage in microfluidic devices and standardize the corresponding safety and performance metrics. There is a need for quantitative metrics to provide quality assurance during or after the manufacturing process. It is also necessary to implement application-specific test methods to effectively characterize leakage in microfluidic systems. In this review, different methods for assessing microfluidics leaks, the benefits of using different test media and materials, and the utility of leakage testing throughout the product life cycle are discussed. Current leakage testing protocols and standard test methods that can be leveraged for characterizing leaks in microfluidic devices and potential classification strategies are also discussed. We hope that this review article will stimulate more discussions around the development of gas and liquid leakage test standards in academia and industry to facilitate device commercialization in the emerging field of microfluidics.